Learning Islamic Religious Education with Multicultural Insights in Strengthening Harmony among Students - Siti Patimah; Badarussyamsi Badarussyamsi; Mahluddin Mahluddin (Center for Religious Studies and Social Empowerment Foundation, 2022)
The objectives of this study include: (1) To find out how the implementation of Islamic Religious Education learning with a multicultural perspective in SMA Negeri 3 Tebo Regency, (2) To find out what obstacles are faced in multicultural-based learning, and (3) To find out how to overcome obstacles multicultural based learning. This research is a descriptive qualitative research. Data was collected by means of observation, interviews, and documentation. The data collected in the form of words were analyzed by means of reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be stated that the learning of Islamic Religious Education with a multicultural perspective is carried out in order to strengthen the harmony of life among students at SMA Negeri Tebo Regency with an emphasis on awareness of the diversity of ethnicity, culture, language, religion, and so on. The obstacle that teachers often encounter is that there are still some students who do not understand multicultural insight so that it often triggers the emergence of expressions and attitudes that offend SARA so that it often causes chaos. In order to overcome the existing diversity, teachers continue to approach students and provide an understanding that multiculturalism is a gift that must be nurtured.